2016
DOI: 10.3233/jrs-160668
|View full text |Cite
|
Sign up to set email alerts
|

Persistent sexual dysfunction after early exposure to SSRIs: Systematic review of animal studies

Abstract: Our results showed substantial and lasting effects on sexual behaviour in rats after exposure to an SSRI early in life on important sexual outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…SSRIs cause sexual dysfunction in a large proportion of users, and more worryingly, some people report that this persists after stopping the drug (Bala, Nguyen, & Hellstrom, 2018). This is consistent with research with young animals finding that sexual behaviour is negatively impacted by previous use of SSRIs (Simonsen, Danborg, & Gotzsche, 2016). The prevalence of persistent effects is unknown, but even if it is rare, it is a potential catastrophe given the huge numbers now using antidepressants, and the increasing number of younger users.…”
Section: Antidepressantssupporting
confidence: 91%
“…SSRIs cause sexual dysfunction in a large proportion of users, and more worryingly, some people report that this persists after stopping the drug (Bala, Nguyen, & Hellstrom, 2018). This is consistent with research with young animals finding that sexual behaviour is negatively impacted by previous use of SSRIs (Simonsen, Danborg, & Gotzsche, 2016). The prevalence of persistent effects is unknown, but even if it is rare, it is a potential catastrophe given the huge numbers now using antidepressants, and the increasing number of younger users.…”
Section: Antidepressantssupporting
confidence: 91%
“…Animal studies have found that exposure to an SSRI during pregnancy or at an early age produces sexual deficits in adulthood [ 42 ]. A recent study in humans found evidence that there may be similar implications for people exposed to an SSRI in childhood [ 43 ].…”
Section: Post-ssri Asexualitymentioning
confidence: 99%
“…; Phillips‐Farfán and Fernández‐Guasti ; Simonsen et al . ). Dopamine levels increase in the NAcS in response to odors emitted by estrus female and during copulation (Pfaus et al .…”
mentioning
confidence: 97%